2018
DOI: 10.1534/g3.117.300394
|View full text |Cite
|
Sign up to set email alerts
|

Germline Variants in the POT1-Gene in High-Risk Melanoma Patients in Austria

Abstract: Risk of melanoma is in part determined by genetic factors. Currently the only established high penetrance familial melanoma genes are CDKN2A and CDK4. Recent studies reported germline variants in POT1 in melanoma families. In the present study, we sequenced the entire POT1 gene in 694 patients from the M3-study. Patients with multiple primary melanomas (n = 163) or with a positive family history (n = 133) were classified as high-risk melanoma patients. Additionally, 200 single primary melanoma patients and 198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…POT1 is a gene involved in telomeres maintenance, a critical function for genome stability, having a significant intolerance to LoF variants (GnomAD v.2.1: observed vs. expected ratio: 0.19). Multiple reports associated POT1 germline variants with various types of familial cancers including chronic lymphocytic leukemia (CLL; Speedy et al, 2016), Hodgkin lymphoma (McMaster et al, 2018), glioma (Bainbridge et al, 2015), melanoma (Muller, Krunic, Wendt, von Haeseler, & Okamoto, 2018; Potrony et al, 2018; Robles‐Espinoza et al, 2014; Shi et al, 2014; Wilson et al, 2017; Wong et al, 2018), cardiac angiosarcoma (Calvete et al, 2015), Li‐Fraumeni‐like syndrome (Calvete et al, 2017) and CRC (Chubb, Broderick, Dobbins, Frampton et al, 2016). Chubb et al, reported the presence of three carriers of Type‐A/B variants among cases: c.219_220insA (p.Asn75LysfsTer16, cpMAF:0%), c.1087C>T (p.Arg363Ter, cpMAF:0.001%) and c.1851_1852delTA (p.Asp617GlufsTer9, cpMAF:0.004%), while no Type‐A/B variants were identified in controls (Chubb, Broderick, Dobbins, Frampton et al, 2016; CanVar).…”
Section: Resultsmentioning
confidence: 99%
“…POT1 is a gene involved in telomeres maintenance, a critical function for genome stability, having a significant intolerance to LoF variants (GnomAD v.2.1: observed vs. expected ratio: 0.19). Multiple reports associated POT1 germline variants with various types of familial cancers including chronic lymphocytic leukemia (CLL; Speedy et al, 2016), Hodgkin lymphoma (McMaster et al, 2018), glioma (Bainbridge et al, 2015), melanoma (Muller, Krunic, Wendt, von Haeseler, & Okamoto, 2018; Potrony et al, 2018; Robles‐Espinoza et al, 2014; Shi et al, 2014; Wilson et al, 2017; Wong et al, 2018), cardiac angiosarcoma (Calvete et al, 2015), Li‐Fraumeni‐like syndrome (Calvete et al, 2017) and CRC (Chubb, Broderick, Dobbins, Frampton et al, 2016). Chubb et al, reported the presence of three carriers of Type‐A/B variants among cases: c.219_220insA (p.Asn75LysfsTer16, cpMAF:0%), c.1087C>T (p.Arg363Ter, cpMAF:0.001%) and c.1851_1852delTA (p.Asp617GlufsTer9, cpMAF:0.004%), while no Type‐A/B variants were identified in controls (Chubb, Broderick, Dobbins, Frampton et al, 2016; CanVar).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, this gene shows a significant intolerance to loss-of-function variants (GnomAD v.2.1.1: LOEUF = 0.362). In the past years, multiple reports associated POT1 germline variants with a predisposition to various types of tumors, including CRC [ 10 , 28 , 62 , 63 , 64 , 65 , 66 ]. Chubb et al identified two carriers of disruptive predicted pathogenic POT1 variants in 1006 CRC patients, while no disruptive variants were identified in 1609 controls [ 28 ].…”
Section: Candidate Causal Genes For Mismatch Repair Proficient Hermentioning
confidence: 99%
“…The protection of telomeres 1 gene (POT1) gene is critical for shelterin complex formation and binding to telomeric ssDNA through its interaction with TPP1 (Henry, Osborne, and Else 2020). POT1 is located at 7q31.33 and variants have been reported at isoform 1 of the protein (Müller et al 2018). Germline mutations in this gene have been implicated in familial melanoma J o u r n a l P r e -p r o o f predisposition in addition to the development of other tumors such as chronic lymphocytic leukemia (CLL), angiosarcomas, and gliomas (Calvete et al 2017).…”
Section: Pot1mentioning
confidence: 99%